Using COBIT-19 to Create Information Assurance of COVID-19 Application - Catur Pamuji, Geraldi; Putra, Yeffry Handoko; Wahdiniwaty, Rahma (Jurnal Tata Kelola dan Kerangka Kerja Teknologi Informasi, 2022)
In the new era of covid-19 Pandemic, there is some COVID-19 Alert system which record patients exposed to covid-19 in around the world and also each provinces of Indonesia. The research goal is to make model to audit the COVID-19 Alert System with the issue of information assurance. The proposed model offers the audit assessment model to calculate the capability system in the perspective of Information Assurance. The method of assessment model is based on COBIT 2019 and also ISO / IEC 15504-2:2003 about requirement for performing Software Process Assessment. The result is the audit model equipped by the design factor for assessment model of COVID-19 Alert System, some process activities of audit and chosen mapping of control objectives to alignment goals for enterprise architect and auditor